Приключения Чипполино: [сказка : перевод с итальянского] / Родари Дж. - Родари Джанни (Чинар, 2021)
Экземпляры: БС (20220414) / Инвентарный номер: РТШ55160 / Сис.шифр: 84(4Ита) / Авт.знак: Р 60 / ГРНТИ: 17.82.93 / ББК: 84(4Ита)-4